2019
DOI: 10.1016/j.exger.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific stress tolerance, proteolysis, and lifespan in the invertebrate Tigriopus californicus

Abstract: Because stress tolerance and longevity are mechanistically and phenotypically linked, the sex with higher acute stress tolerance might be expected to also live longer. On the other hand, the association between stress tolerance and lifespan may be complicated by tradeoffs between acute tolerance and long-term survival. Here we use the copepod Tigriopus californicus to test for sex differences in stress resistance, proteolytic activity and longevity. Unlike many model organisms, this species does not have sex c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 108 publications
(124 reference statements)
9
34
0
Order By: Relevance
“…This suggests that at least a portion of the genetic differentiation among populations is likely adaptive. Moreover, several common-garden studies in laboratoryraised individuals have demonstrated differences in upper and lower thermal tolerance limits that are consistent with local thermal adaptation in response to the latitudinal temperature gradient across the species range (Willett, 2010;Kelly et al, 2012;Wallace et al, 2014;Pereira et al, 2014Pereira et al, , 2017Leong et al, 2018;Willett and Son, 2018;Foley et al, 2019). This variation among populations has also been associated with genetically based differences in the function and regulation of heat shock protein genes (Schoville et al, 2012;Barreto et al, 2015;Tangwancharoen et al, 2018) and in the maintenance of mitochondrial ATP synthesis rates at high temperatures (Harada et al, 2019).…”
Section: Introductionmentioning
confidence: 87%
“…This suggests that at least a portion of the genetic differentiation among populations is likely adaptive. Moreover, several common-garden studies in laboratoryraised individuals have demonstrated differences in upper and lower thermal tolerance limits that are consistent with local thermal adaptation in response to the latitudinal temperature gradient across the species range (Willett, 2010;Kelly et al, 2012;Wallace et al, 2014;Pereira et al, 2014Pereira et al, , 2017Leong et al, 2018;Willett and Son, 2018;Foley et al, 2019). This variation among populations has also been associated with genetically based differences in the function and regulation of heat shock protein genes (Schoville et al, 2012;Barreto et al, 2015;Tangwancharoen et al, 2018) and in the maintenance of mitochondrial ATP synthesis rates at high temperatures (Harada et al, 2019).…”
Section: Introductionmentioning
confidence: 87%
“…Sex is an additional consideration in studies of adult copepods. Female copepods usually have longer lifespans and higher stress resistances than males (e.g., Foley et al, 2019;Parrish and Wilson, 1978). This difference in resistance, and other physiological differences associated with reproduction may result in different transcriptional responses to stressors.…”
Section: Selection Of Developmental Stagementioning
confidence: 99%
“…Additionally, sex-specific thermal effects may also generate breakdowns in sexual communication in the wake of global warming. While males and females within a species are often assumed to react similarly to environmental stressors like temperature (Shreve et al, 2004), sex-specific thermal responses in courtship activity could arise through sex differences in body size and thermoregulatory behavior during reproduction (Brown and Weatherhead, 2000;Matzkin et al, 2009;Darnell et al, 2013;Baudier et al, 2015;Foley et al, 2019). If reproductive activity levels across temperatures are sex-specific, shifts in temperatures could accentuate mismatches in male and female activity levels and reduce overlap when both sexes are actively seeking mates.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to species-specific responses to temperature, we might predict that males and females respond differently to temperature due to underlying sex-specific physiology (Brown and Weatherhead, 2000;Matzkin et al, 2009;Darnell et al, 2013;Baudier et al, 2015;Foley et al, 2019). However, courtship activity results from a complex interaction between physiology and behavioral decisions, and we currently lack a complete framework for making an informed prediction about sex-specific responses to temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation